2016
DOI: 10.3390/nu8110714
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characterization of Self-Reported Gluten Sensitivity in The Netherlands

Abstract: Background: A growing number of individuals reports symptoms related to the ingestion of gluten-containing food in the absence of celiac disease. Yet the actual prevalence is not well established. Methods: Between April 2015 and March 2016, unselected adults visiting marketplaces, dental practices and a university in The Netherlands were asked to complete a modified validated questionnaire for self-reported gluten sensitivity (srGS). Results: Among the 785 adults enquired, two had celiac disease. Forty-nine (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
69
2
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 31 publications
8
69
2
6
Order By: Relevance
“…9 This is in line with similar studies from the US, Chile, United Kingdom and Europe that demonstrated a population prevalence of self-reported wheat or gluten sensitivity of between 4% and 13%. [9][10][11][12][13][14] This suggests that a gluten-sensitive condition, separate to coeliac disease and wheat allergy, may be responsible for their symptoms. This condition has attracted increasing international attention and has been labelled non-coeliac gluten sensitivity.…”
mentioning
confidence: 99%
“…9 This is in line with similar studies from the US, Chile, United Kingdom and Europe that demonstrated a population prevalence of self-reported wheat or gluten sensitivity of between 4% and 13%. [9][10][11][12][13][14] This suggests that a gluten-sensitive condition, separate to coeliac disease and wheat allergy, may be responsible for their symptoms. This condition has attracted increasing international attention and has been labelled non-coeliac gluten sensitivity.…”
mentioning
confidence: 99%
“…Over 75% of these patients have HLA-DQ2 and / or HLA-DQ8.75% of these patients carry HLA-DQ2 and/ or HLA-DQ8 (43) . NCGS can be defined to describe individuals who complain of intestinal and extra-intestinal symptoms related to gluten intake and report rapid improvement after withdrawal of these foods from the diet, and in which both the diagnosis of CD and wheat allergy are discarded (45,52,53,58,(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73) . This fact raises many unanswered questions.…”
Section: Iii-gluten Related Disorders -Ncgs and Ibsmentioning
confidence: 99%
“…However, incomplete knowledge of the etiopathogenesis of these clinical conditions, lack of data on their real epidemiology, as well as the absence of a gold standard for their diagnosis, make the overall picture difficult to understand (22,(27)(28)(34)(35)(36)(37)44,45,57,58,(61)(62)(63) . Gluten, wheat and related proteins (e.g., amylase-trypsin inhibitors, and fermentable oligo-di-mono-saccharides and polyols (FODMAPs) are the most relevant IBS symptom triggers, although the true 'culprit(s)' is/are still not well established (52,61,63,68,72,73) . In addition, Rome IV criteria seem unable to exclude an underlying possible IBS-like disorder.…”
Section: Iii-gluten Related Disorders -Ncgs and Ibsmentioning
confidence: 99%
“…Since specific diagnostic markers are missing, the large majority of data on NCGS are based on patients’ self-reported gluten-induced symptoms. Several studies tried to estimate the prevalence of NCGS: one of the first reports comes from the Center for Celiac Research at the University of Maryland (USA) reporting a prevalence of gluten avoidance of approximately 6% in a population of patients with GI symptoms seen at a tertiary center [9], while other reports indicate a prevalence of 0.5 up to 10% in a general population [10-13]. All studies show a clear predominance of women.…”
Section: Epidemiological Studies On Ncgsmentioning
confidence: 99%